2009
DOI: 10.1111/j.1365-2036.2008.03904.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: intravenous pantoprazole vs. ranitidine for the prevention of peptic ulcer rebleeding: a multicentre, multinational, randomized trial

Abstract: SUMMARY BackgroundControlled pantoprazole data in peptic ulcer bleeding are few.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…Many well-conducted, randomized controlled trials, metaanalyses, and consensus conferences have confirmed the efficacy of endoscopic therapy in this setting (Sacks HS et al 1990;Cook DJ et al, 1992). These data supported a reduction in recurrent bleeding, the need for urgent surgery, and mortality in patients with high-risk stigmata (Barkun et al, 2003;Adler et al, 2004). However, most of these studies were conducted before the widespread use of PPIs, and predominantly used injection therapy, bipolar-probe coagulation therapy, or a combination of injection and coagulation therapy.…”
Section: Therapeutic Endoscopymentioning
confidence: 71%
See 3 more Smart Citations
“…Many well-conducted, randomized controlled trials, metaanalyses, and consensus conferences have confirmed the efficacy of endoscopic therapy in this setting (Sacks HS et al 1990;Cook DJ et al, 1992). These data supported a reduction in recurrent bleeding, the need for urgent surgery, and mortality in patients with high-risk stigmata (Barkun et al, 2003;Adler et al, 2004). However, most of these studies were conducted before the widespread use of PPIs, and predominantly used injection therapy, bipolar-probe coagulation therapy, or a combination of injection and coagulation therapy.…”
Section: Therapeutic Endoscopymentioning
confidence: 71%
“…Proton pump inhibitors initiated after endoscopic haemostasis of bleeding peptic ulcer significantly reduced rebleeding compared with placebo or H 2 -receptor antagonists (Sung et al, 2009;van Rensburg et al, 2009). The initiation of PPIs before endoscopy significantly decreases the proportion of patients with stigmata of a recent bleed (e.g.…”
Section: Pharmacotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Antisecretory drugs such as proton pump inhibitors (PPIs) or histamine H2 receptor antagonists are effective in preventing the upper GI bleeding induced by the concomitant use of antiplatelet drugs with NSAIDs and low-dose ASA. [5][6][7][8] The antiplatelet drug clopidogrel is a prodrug, the actions of which may be related to adenosine diphosphate (ADP) receptors on platelet cell membranes. 9 This drug specifically and irreversibly inhibits the P2Y12 subtype of the ADP receptor, which is important for the aggregation of platelets and cross-linking by the protein fibrin.…”
Section: Introductionmentioning
confidence: 99%